PERSEPSI KEADILAN PAJAK TERHADAP PERILAKU KEPATUHAN WAJIB PAJAK ORANG PRIBADI (WPOP) - Dian Anggraeni Berutu; Puji Harto (Diponegoro Journal of Accounting, 2013)
This research aimed to examine the perception of tax fairness dimensions on tax compliance behaviour of individual tax payer. Richardson and Giligant (2005) identified five of tax fairness dimension: general fairness and distribution of tax burden, exchanges with the government, special provisions, preferred tax rate structure, and self interest towards individual tax payers compliance. This study used a questionnaire survey design as an instrument.            In this study, a sample of individual tax payers is working as an entrepreneur various industries, civil servants (PNS) and private sector employees. The number of samples used are 118 individual tax payers. Sampling technique in this research  using purposive sampling techniques (based on criteria samples). The method of analysis used in this research is multiple regression.            The findings of this research show that (1) the structure of the preferred tax rates (preferred tax rate structures) positive effect on the level of individual taxpayer compliance significantly and (2) personal interest (self-interest) positive effect on the level of individual taxpayer compliance significantly.